Differences in physical activity levels of school domains between high- and low-active adolescents - Arieli Fernandes Dias; Caroline Brand; Vanilson Batista Lemes; Cíntia Mussi Alvim Stocchero; Cesar Agostinis-Sobrinho; Michael J Duncan; Jorge Mota; Anelise Reis Gaya; Adroaldo Cezar Araujo Gaya (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: To compare high active (HA) and low active (LA) adolescent's physical activity (PA) levels in three different domains: commuting to school, physical education (PE) class and recess time at school. Method: This is a cross-sectional study, with a quantitative approach and random sample of 176 (105 girls) adolescents aged 14 - 18 years old from 10 urban public high schools in southern from Brazil. PA levels were measured using a pedometer. The average number of steps was recorded on the way to school, during PE classes and during school recess time. Participants were classified as HA and LA according to Tudor-Locke's cut-off points. Data were analyzed using descriptive statistics and One-Way ANOVA stratified by sex. Results: Data showed differences of mean values between school commuting PA for girls (LA: 1057.60; HA: 1624.54; Δ: 566.94; p<0.001), during PE class (LA: 1401.75, HA: 1701.10; Δ: 308.53; p<0.05) and in recess time (LA: 443.09, HA: 611.98; Δ: 168.89; p=0.001), whereas for boys, differences only found between the mean values of PA during PE class (LA: 1787.91, HA: 2511.20; Δ: 723.29; p<0.01). Conclusion: HA girls are consistently more active in each domain analyzed compared to LA counterparts, while for boys PE class was the domain that differentiated the HA vs. LA adolescents. This study highlights some potential settings to be included in the policies focused in enhance PA levels among adolescents namely in the context of school PE.